Cloud AI for Regulatory Compliance and Risk Management in Financial Institutions - Sankaralingam, Kuthalingam (International Journal of Computing and Engineering, 2025)
Purpose: The financial services industry is increasingly adopting artificial intelligence (AI) solutions hosted in the cloud to meet the dual imperatives of regulatory compliance and effective risk management. Methodology: AWS Cloud AI offers scalability, adaptability, and advanced analytics that enable financial institutions to monitor, detect, and respond to regulatory and risk-related challenges in near real-time. This paper explores the integration of AWS cloud-based AI technologies in regulatory compliance and risk management within financial institutions. Findings: It provides a comprehensive overview of the current landscape, discusses prominent use cases, presents a framework for analyzing real-world applications, and outlines future directions. Unique Contribution to Theory, Practice, and Policy: The financial services industry is increasingly adopting artificial intelligence (AI) solutions hosted in the cloud to meet the dual imperatives of regulatory compliance and effective risk management. AWS Cloud AI offers scalability, adaptability, and advanced analytics that enable financial institutions to monitor, detect, and respond to regulatory and risk-related challenges in near real-time. This paper explores the integration of AWS cloud-based AI technologies in regulatory compliance and risk management within financial institutions. It provides a comprehensive overview of the current landscape, discusses prominent use cases, presents a framework for analyzing real-world applications, and outlines future directions.